Keeping it Safe: Home and Personal Safety, Fire Extinguishers, Smoke Detectors, Ground Fault Circuit Interrupters, Carbon Monoxide Detectors - Mary N. Harrison (EDIS)
There are several items that you should have to protect your family and home, such as: a fire extinguisher, smoke detectors, Ground Fault Circuit Interrupters (GFCIs), carbon monoxide detectors, and locks on your doors and windows. This document is FCS5233-05, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.